Uso de Midazolam intramuscular versus Diazepam intravenoso en pacientes pediátricos con estado epiléptico convulsivo en el Hospital Regional Docente de Trujillo, enero 2020 – diciembre 2020 - Aspauza Lescano, Tahireh (2021)
Status epilepticus in children is a neurologic emergency with significant morbidity and must be treated in a timely manner to avoid irreversible neuronal damage. Benzodiazepines are the first-line treatment, which in turn differ in some effects, which may lead us to choose one over the other based on their ability to stop seizures, their route of administration, as well as its adverse effects. The present research work is a single-center randomized controlled clinical trial that aims to determine the effectiveness of the use of intramuscular Midazolam compared with intravenous diazepam for the treatment of convulsive status epilepticus in patients admitted to the pediatric emergency department of the Trujillo Regional Teaching Hospital. between January and December 2020. The average time to seizure cessation and the adverse effects of each drug will be analyzed to establish its effectiveness.